Orthopaedic manifestations within the 22q11.2 Deletion syndrome: A systematic review. Issue 10 (21st November 2017) - Homans, Jelle F.; Tromp, Isabel N.; Colo, Dino; Schlösser, Tom P. C.; Kruyt, Moyo C.; Deeney, Vincent F. X.; Crowley, Terrence B.; McDonald‐McGinn, Donna M.; Castelein, René M.
Abstract : The 22q11.2 Deletion Syndrome (22q11.2DS) is the most common microdeletion syndrome with an estimated prevalence of 1:4, 000 live births. 22q11.2DS is known to have wide phenotypic variability, including orthopaedic manifestations. The purpose of this systematic review is to increase the awareness of orthopaedic manifestations associated with 22q11.2DS. This systematic review was performed according to the PRISMA Guidelines. Original epidemiological studies on the prevalence of orthopaedic manifestations within 22q11.2DS were systematically searched for in PubMed and EMBASE. The included articles were scored according to a risk‐of‐bias tool, a best‐evidence synthesis was performed and the prevalence data was extracted. Sixty‐nine published manuscripts described 58 orthopaedic manifestations in a total of 6, 055 patients. The prevalence of at least one cervical or occipital anomaly is 90.5–100% (strong evidence). Fourteen studies ( n  = 2, 264) revealed moderate evidence for a wide scoliosis prevalence of 0.6–60%. Two studies demonstrated that 5–6.4% of all 22q11.2DS patients required surgical scoliosis correction. Fifteen studies ( n  = 2, 115) reported a 1.1–13.3% prevalence of clubfoot with moderate evidence. Other reported orthopaedic manifestations are patellar dislocation (10–20%), juvenile rheumatic arthritis (3.75%), impaired growth and skeletal anomalies like polydactyly (1.0–3.7%), syndactyly (11–11.8%), butterfly vertebrae (11.1%) and 13 ribs (2–19%). Orthopaedic findings are important manifestations of the 22q11.2DS, both in bringing patients to diagnostic attention and in requiring surveillance and appropriate intervention. Data on these manifestations are scattered and incomprehensive. Routinely screening for cervical anomalies, scoliosis, and upper and lower limb malformations is recommended in this vulnerable group of patients.